Implementing the DIKW model on complex deep-level mine compressor systems - Mohammad, Asadullah (Stellenbosch : Stellenbosch University, 2025)
Mohammad, A. 2025. Implementing the DIKW model on complex deep-level mine compressor systems. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/85a0c4da-30fc-4e00-a6fc-29e097b4c90e